If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 218 = 119 + -1x Solving 218 = 119 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 218 + x = 119 + -1x + x Combine like terms: -1x + x = 0 218 + x = 119 + 0 218 + x = 119 Add '-218' to each side of the equation. 218 + -218 + x = 119 + -218 Combine like terms: 218 + -218 = 0 0 + x = 119 + -218 x = 119 + -218 Combine like terms: 119 + -218 = -99 x = -99 Simplifying x = -99
| 7.30=4x+6 | | 4r+3=10 | | 1.3x-5.4x-5.4x+3= | | 35-3x=10+6x | | 1.3h-4(2.3h-3)=2.3h-6 | | 5x+7y=300solvey | | 2(5z+2)-3(z+1)= | | -11r-3+12r+2= | | 0=2x^2-3x-104 | | x+x+3=31 | | 12x=10+2 | | z=(x-4)k | | 8r^3+24r^2=32r | | 2.2n+4-9-4.5n= | | 6y(6-x)= | | -4m+14=-2m-10 | | 5/6+6/12-22-2= | | 180=x^3+x^2 | | (9+j)+6=jwhatisJ | | 7u=2u+15 | | 145+36=433 | | 2(x+3y)-4(2x-8y)= | | 2(x-3)+5=3(z-1) | | Z(2z-9)(z+3)=0 | | 0.6(x+20)+08(x-10)=46 | | 5x-2(x+3)=40 | | 10=40-3x | | 6x-4x+13=27+2x | | (2x+3)(x+1)-3(x+2)(x+1)=-3(x+5) | | 100g+8= | | 6(94X-8)+3X=141 | | 9+g=-14 |